Truly Exceptional? Participants in the Belgian 2019 Youth for Climate Protest Wave - Wouters, Ruud; de Vydt, Michiel; Staes, Luna (Politics of the Low Countries, 2025)
In 2019, the world witnessed an exceptional wave of climate protests. In this case study, we scrutinise who participated in the protests staged in Belgium. We ask: did the exceptional mobilising context of the 2019 protest wave also bring exceptional protesters to the streets? Were thanks to the unique momentum standard barriers to protest participation overcome? We answer these questions by comparing three surveys of participants in the 2019 protest wave with three surveys of relevant reference publics. Our findings show that while the Belgian 2019 protest was in many ways exceptional, its participants were less so. Although participants – especially in the early phase of the protest wave – were less protest experienced, younger and unaffiliated to organisations, our findings simultaneously confirm the persistence of a great many well-known socio-demographic and political inequalities. Our conclusion centres on the implications of these findings.